Ruptura prematura de mebranas y su relación con sepsis neonatal en recién nacidos ingresados al servicio de neonatología del Hospital Isidro Ayora 2013. - Sarango Ramos, Elizabeth María. (2014)
Premature rupture of membranes was defined as leakage of amniotic fluid through a discontinuity of the egg membranes before the onset of labor is associated with various factors such as maternal infections , multiparity , socio low economic status , smoking, invasive procedures , low BMI , Deficiency of vitamin C and E1 ; The RPM is directly associated with the development of neonatal sepsis as a result of pollution from upstream pathway or by direct contact thus causing secondary infections and vertical to it a potentially infected RN and more likely to develop sepsis transmission. With this background a descriptive , prospective study was conducted ; in order to know the relationship of premature rupture of membranes and neonatal sepsis in newborns admitted to the Isidro Ayora Hospital in June to October 2013 period , addition establish risk factors associated with maternal and gestational age with the development of sepsis, and verification of sepsis by MOH scale . The information was obtained through the collection of data from medical records by a tab. 37 cases of RPM to which risk factors among key associated We analyzed; 73% infections; multiparity 51.3 % and 18.9 % inadequate prenatal care . Frequencies of 9 cases of neonatal sepsis were identified representing 24.4%; of which 55% was found for prematurity. Finally with the use of MSP sepsis scale, 100% unlikely sepsis cases studied were shown Keywords: Premature Rupture of Membranes, Sepsis